2021
DOI: 10.1097/acm.0000000000004366
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Use of Workplace-Based Assessment in Clinical Learning Environments: A Scoping Review

Abstract: Workplace-based assessment (WBA) serves a critical role in supporting competency-based medical education (CBME) by providing assessment data to inform competency decisions and support learning. Many WBA systems have been developed, but little is known about how to effectively implement WBA. Filling this gap is important for creating suitable and beneficial assessment processes that support large-scale use of CBME. As a step toward filling this gap, the authors describe what is known about WBA implementation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 172 publications
2
23
0
1
Order By: Relevance
“…For example, building programs of WBA or frameworks to assess professionalism requires deep and meaningful engagement with assessors and learners to co-design new systems and approaches that are contextually specific. 10,14,15 Co-design is also relevant when considering how advanced technology can be applied to the future of medical education. The RIME supplement highlights work related to AI and machine learning, while noting that innovations can be enhanced when past experiences are included in their application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, building programs of WBA or frameworks to assess professionalism requires deep and meaningful engagement with assessors and learners to co-design new systems and approaches that are contextually specific. 10,14,15 Co-design is also relevant when considering how advanced technology can be applied to the future of medical education. The RIME supplement highlights work related to AI and machine learning, while noting that innovations can be enhanced when past experiences are included in their application.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al's scoping review on the implementation of workplace-based assessments (WBAs) highlights the need to take a broader view of our assessment initiatives beyond the level of just the tool. 14 Considering one's local context, the theoretical rationale for implementation, and addressing the barriers are just as significant for the success of assessment programs as the accompanying validity evidence. Anderson's review also shows the limits of the current approaches to studying assessment tools at single institutions or context which limits both practical and theoretical generalizabilities as we seek to develop a strong empirical basis for WBA programs.…”
Section: Assessments As Tools As Systems and Social Technologiesmentioning
confidence: 99%
“…Entrustment scales ( Table 1 ) were used in the mini-CEX, DOPS, and PBA. [ 9 ] However, in the CBD, performance descriptors ( Table 2 ) were used. Feedback was recorded by the staff and self-evaluation was recorded by the students.…”
Section: Methodsmentioning
confidence: 99%
“…The scoping review by Chan et al [ 8 ] recommended that more work must be done to provide stronger evidence on both quantitative and qualitative data collected using the WBA. Moreover, the scoping review by Andreson et al [ 9 ] revealed that a limited number of studies discussed the role of subjectivity and bias in WBAs at the level of individual assessors. Andreson et al [ 9 ] recommended further research studying subjectivity while using the WBA tools to fill the gaps in knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation